Child Abuse and Neglect A Multidimensional Approach - Muela, Alexander (IntechOpen, 2012)
Child maltreatment constitutes a social problem that affects all societies of the world. A recent study by the World Health Organisation points out that millions of children suffer some form of maltreatment and require medical and social attention. Therefore, child maltreatment is not a new phenomenon; it has been around since the beginning of time. Child maltreatment is recognized as an important psychopathological risk factor and is associated with poor psychological function in childhood and adolescence and adulthood. The aim of this book is to address the issue of child abuse and neglect from a multidimensional perspective. The reader will find a selection of internationally recognized works addressing the issue of child maltreatment both from theoretical and applied view.